Single-cell transcriptome analysis reveals aberrant stromal cells and heterogeneous endothelial cells in alcohol-induced osteonecrosis of the femoral head - Zheting Liao; Yu Jin; Yuhao Chu; Hansen Wu; Xiaoyu Li; Zhonghao Deng; Shuhao Feng; Nachun Chen; Ziheng Luo; Xiaoyong Zheng; Liangxiao Bao; Yongqing Xu; et al. (Communications Biology, 2022)
Single-cell RNA-seq of bone from patients with osteonecrosis of the femoral head (ONFH) highlights the relevance of stromal and endothelial cells to disease pathogenesis, and provides a resource for developing cell type-specific therapeutic strategies.